Evaluation of different antimicrobial stewardship models at a rehabilitation hospital: An interrupted time series (ITS) study. Issue 1 (21st March 2022) - Curran, Jennifer A.; Leis, Jerome A.; Robinson, Larry; Daneman, Nick; Wan, Michael; Mistry, Asha; Zhang, Sara; Massey, Mridula; Lam, Wendy; Jong, Grace; Elligsen, Marion; Lam, Philip W.
Abstract: Objective: To evaluate different prospective audit-and-feedback models on antimicrobial prescribing at a rehabilitation hospital. Design: Retrospective interrupted time series (ITS) and qualitative methods. Setting: A 178-bed rehabilitation hospital within an academic health sciences center. Methods: ITS analysis was used to analyze monthly days of therapy (DOT) per 1, 000 patient days (PD) and monthly urine cultures ordered per 1, 000 PD. We compared 2 sequential intervention periods to the baseline: (1) a period when a dedicated antimicrobial stewardship (AMS) pharmacist performed prospective audit and feedback and provided urine culture education followed by (2) a period when ward pharmacists performing audit and feedback. We conducted an electronic survey with physicians and semistructured interviews with pharmacists, respectively. Results: Audit and feedback conducted by an AMS pharmacist resulted in a 24.3% relative reduction in total DOT per 1, 000 PD (incidence rate ratio [IRR], 0.76; 95% confidence interval [CI], 0.58–0.99; P = .04), whereas we detected no difference between ward pharmacist audit and feedback and the baseline (IRR, 1.20; 95% CI, 0.53–2.70; P = .65). We detected no statistically significant change in monthly urine-culture orders between the AMS pharmacist period and the baseline (level coefficient, 0.81; 95% CI, 0.65–1.01; P = .07). Compared to baseline, the ward pharmacist period showed a statistically significant increase in urine-culture ordering over time (slope coefficient, 1.04; 95% CI, 1.01–1.08; P = .02). The barrier most identified by pharmacists was insufficient time. Conclusions: Audit and feedback conducted by an AMS pharmacist in a rehabilitation hospital was associated with decreased antimicrobial use.